Addressing osteoblast senescence: Molecular pathways and the frontier of anti‐ageing treatments - Zhengdong Zhang; Pan Liu; Yu Song; Liang Ma; Yan Xu; Jie Lei; Bide Tong; Dingchao Zhu; Huaizhen Liang; Hongchuan Wang; Xingyu Zhou; Zixuan Ou; et al. (Clinical and Translational Medicine, 2025)
Abstract Background Osteoblast senescence is a central driverof age‐related osteoporosis. Accumulating evidence shows that counteractingthis senescence can substantially mitigate bone loss. In this review, we summarize the hallmarks of osteoblast senescence, the signaling pathways involved, and therapeutic strategies that target osteoblast senescence tocombat age‐related osteoporosis. Methods Chronic diseases associated with ageingpose a significant threat to human health. Studies have shown that osteoporosisis closely linked to the ageing process of the body and the senescence ofosteoblasts within the bone microenvironment. Counteracting the senescence ofosteoblasts and maintaining the balance of differentiation, proliferation andfunction between osteoclasts and osteoblasts has been a key focus in the research of age‐related osteoporosis and bone loss. The biological behaviour andfunctionality of the osteoblast lineage related to senescence are modulated bya variety of targets, including signalling pathways, proteins and genes associated with ageing. This review aims to discuss the senescence‐related characteristics of the osteoblast lineage, dissect the interplay and mechanisms between it and ageing‐associated signalling pathways, proteinsand genes, as well as current strategies for the prevention and treatment ofosteoblast senescence. Conclusion This review systematically examines the regulatory interactions among markers, therapeutic targets, and signalingpathways associated with osteoblast senescence, alongside current potential strategies for targeting this process. It provides more comprehensive information for future research into the complex mechanisms underlying age‐related osteoporosis driven by osteoblast senescence. Key points Osteoblast senescence is a key driver of age‐related osteoporosis, disrupting bone formation and homeostasis. Aging impacts osteoblasts through multiple pathways, including telomere shortening, genomic instability, SASP secretion, and others. Bone loss related to osteoblast senescence involves the activation and crosstalk of multiple signaling pathways. The options for combating and treating osteoblast senescence toachieve anti‐osteoporosis are numerous, but still challenging.